Road accidents, risk and biological factors : the portuguese case - Donário, Arlindo Alegre (2017)
ln Portugal like in many other countries, automotive accidents are the cause of thousands of casualties and the primary source of considerable moral and material damages. The dilemma goes beyond statistical data and numbers, which cannot quantify complex aspects such as pain and suffering and the disability and unanticipated death. As reported by Mohan et ai: "Any road traffic system is highly complex and can be hazardous to human health. Elements of the system include motor vehicles, roads, and road users along with their physical, social and economic environments. Making a road traffic system less hazardous requires a systems approach - understanding the system as a whole and the interaction between its elements, and identifying where there is potential for intervention" (Mohan et ai, 2006:25).